PERBEDAAN KADAR ASAM URAT TIKUS PUTIH (Rattus norvegicus) SETELAH PEMBERIAN KACANG TANAH (Arachis hypogaea L.) - Nabila Nuranjumi; agustyas tjiptaningrum; sofyan musyabiq; hanna mutiara (CV. Jasa Sukses Abadi, 2022)
The excessive uric acid levels in the body can increase the risk of hyperuricemia. The formation of uric acid starts from the synthesis of purines which produce inosine, adenine and guanine monophospate that will be degraded into uric acid. Peanuts contain purines so if it is consumed in excess, it can increase blood uric acid levels. To know the difference in the average blood uric acid levels of rats given peanuts at a dose of 1gr/200grBB, 2gr/200grBB, 4gr/200grBB and not given peanuts. This research used experimental research with post test control group design approach. The sample in this research used 28 rats that divided into 4 groups; K1 were only given standard feed, P1 were given 1gr / 200grBB peanuts, P2 were given 2gr/200grBB peanuts and P3 were given 4gr/200grBB peanuts in everyday for 28 days. Then measuring the blood uric acid levels of rats. The average blood uric acid level of rats before intervention (K1) is 3,28mg/dl, and after intervention is 3,87mg/dl (P1), 4,20mg/dl (P2) and 5,03mg/dl (P3). There is a significant difference between P2 and K1 (p=0,005 ), P3 and K1 (p=0,000 ). There is no a significant difference between P1 and K1 (p=0,130 ). There is a significant difference in the average blood uric acid level of rats given peanuts at a dose of 2gr/200grBB, 4gr/200grBB and not given peanuts. There is no significant difference in the average blood uric acid level of rats given peanuts at a dose of 1gr/200grBB and not given peanuts.